Turning inside Out? Globalization, Neo-liberalism and Welfare States - Clarke, John (Anthropologica, 2022)
Apocalyptic accounts of globalization bringing about the end of the welfare state (and the nation state) have been countered by political-institutionalist views of adaptation. Such views treat globalization as an external force, or pressure, rather than a set of processes that are also internalized within nations. I argue that a more differentiated view of globalization can reveal how it has unsettled welfare state/nation state formations. In the process, taken-for-granted meanings and boundaries of nation-state-welfare have been destabilized. I conclude by suggesting that these processes have made citizenship a distinctive focus of political tensions and conflicts.